Empowering Pregnant Women through Education, PISBRO Cookies, and Family Support to Improve Hemoglobin in Bangun Rejo Village: Pemberdayaan Ibu Hamil melalui Edukasi, Cookies PISBRO, dan Dukungan Keluarga untuk Meningkatkan Hemoglobin di Desa Bangun Rejo - Damayanty S; Erin Padilla Siregar; Henny Rista; Diah Pitaloka; Madiha Aini Raihan; Misno Misno (Room of Civil Society Development, 2026)
Maternal anemia remains an important public health problem that increases the risk of adverse pregnancy outcomes and contributes to factors associated with impaired fetal growth. This community empowerment program aimed to empower pregnant women through the utilization of PISBRO cookies as a complementary food to support hemoglobin improvement and reduce risk factors for stunting. The program was implemented in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency, Indonesia, using a community empowerment approach that included health education, PISBRO cookie production training, consumption of PISBRO cookies together with iron supplementation, adherence monitoring, family support, and pre- and post-program hemoglobin assessment. Twenty-two pregnant women were recruited, and 20 completed the program. Mean adherence to PISBRO cookie consumption was 82.34±13.51%, with 65% of participants categorized as adherent, while 50% received good family support. Mean hemoglobin increased from 9.64±0.42 g/dL to 9.87±0.53 g/dL, with an average increase of 0.24±0.21 g/dL. Ninety percent of participants experienced increased hemoglobin levels, and Wilcoxon signed-rank testing demonstrated a significant difference before and after the program (p<0.001). The integrated community empowerment program combining PISBRO cookies, health education, iron supplementation, adherence monitoring, and family involvement showed potential to support early improvement in maternal hemoglobin. Greater family engagement and sustained follow-up are recommended to enhance program effectiveness.